2015
DOI: 10.1139/apnm-2014-0228
|View full text |Cite
|
Sign up to set email alerts
|

Acute dietary nitrate supplementation does not augment submaximal forearm exercise hyperemia in healthy young men

Abstract: Despite the popularity of dietary nitrate supplementation and the growing evidence base of its potential ergogenic and vascular health benefits, there is no direct information about its effects on exercising limb blood flow in humans. We hypothesized that acute dietary nitrate supplementation from beetroot juice would augment the increases in forearm blood flow, as well as the progressive dilation of the brachial artery, during graded handgrip exercise in healthy young men. In a randomized, double-blind, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
5
25
1
4
Order By: Relevance
“…Results from a meta‐analysis (Siervo, Lara, Ogbonmwan, & Mathers, ) showed that in healthy subjects, acute and chronic inorganic nitrate supplementation induces a 4.4 mmHg mean reduction in systolic blood pressure. Similar to the present study, however, several studies, especially including healthy young adults, reported no effect of NO precursor supplementation on resting blood pressure (Kim et al., ; Le Roux‐Mallouf et al., ; Wightman et al., ). There are several possible explanations for these contrasting results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Results from a meta‐analysis (Siervo, Lara, Ogbonmwan, & Mathers, ) showed that in healthy subjects, acute and chronic inorganic nitrate supplementation induces a 4.4 mmHg mean reduction in systolic blood pressure. Similar to the present study, however, several studies, especially including healthy young adults, reported no effect of NO precursor supplementation on resting blood pressure (Kim et al., ; Le Roux‐Mallouf et al., ; Wightman et al., ). There are several possible explanations for these contrasting results.…”
Section: Discussionsupporting
confidence: 85%
“…() have shown that acute beetroot juice consumption increased human muscle blood flow during moderate‐to high‐intensity handgrip exercise via local vasodilatation. Previous studies (Craig, Broxterman, Smith, Allen, & Barstow, ; Kim et al., ), measuring muscle oxygenation by NIRS in healthy humans during local exercise, have not found a positive effect of acute nitrate supplementation. There are several observations that merit discussion.…”
Section: Discussionmentioning
confidence: 86%
“…We did not collect plasma samples for NO3 or NO2 from subjects who received the placebo shots since previous studies clearly indicate that there is no change in plasma concentrations of NO3 and NO2 following placebo (NO3 free) BR ingestion (Kim et al. ; Lansley et al. ; Wylie et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Kim et al. ) using acute NO3 supplementation via BR have failed to replicate these findings in rats. Although it is unclear why these studies did not demonstrate an increase in exercising muscle blood flow, issues related to the magnitude of increase in plasma NO2, as well as exercise intensity and/or exercise duration may have contributed.…”
Section: Introductionmentioning
confidence: 97%
“…A randomized cross-over double-blind study in 14 healthy volunteers demonstrated that, while an 8 mmol dose of KNO 3 improved PWV and reduced BP measured 3 h following ingestion, no change in the FMD response was evident [115]. More recently, Kim and coworkers in a study assessing the increase in flow and brachial artery diameter following hand-grip exercise in healthy volunteers, also demonstrated improved PWV but no effect on endothelial function with dietary NO 3 − administration [118]. These observations contrast with two other published studies.…”
Section: No 2 − /No 3 − and Vascular Functionmentioning
confidence: 99%